Millerocaulis zamunerae sp. nov. (Osmundaceae) from Jurassic, geothermally influenced, wetland environments of Patagonia, Argentina. Issue 4 (1st October 2016) - Sagasti, Ana Julia; Massini, Juan García; Escapa, Ignacio H.; Guido, Diego M.; Channing, Alan
Abstract : Sagasti, A.J., García Massini, J., Escapa, I.H., Guido, D.M. & Channing, A., August 2016. Millerocaulis zamunerae sp. nov. (Osmundaceae) from Jurassic geothermally influenced wetland environments of Patagonia, Argentina. Alcheringa 40, xxx–xxx. ISSN 0311-5518 A new species of Millerocaulis Erasmus ex. Tidwell emend. Vera is defined based on several permineralized stems recovered from geothermally influenced chert deposits in the Middle–Late Jurassic La Matilde Formation (Santa Cruz, Argentina). Millerocaulis zamunerae sp. nov. is characterized by the presence of an ectophloic dictyoxylic siphonostele, inner parenchymatic and outer sclerotic cortices, homogeneous sclerotic ring in the petiole bases, two masses of sclerenchyma lining the concavity of the petiolar vascular bundle, petiolar inner cortex with sclerenchyma strands in the outermost petiole cycles and stipular wings having one large and several smaller sclerenchyma bundles. Millerocaulis zamunerae inhabited geothermal wetlands and other hot-spring-related sedimentary facies associated with the La Bajada epithermal deposit. Reference to active geothermal wetlands, analogous living plants and other fossil hot spring ecosystems suggest the plant's tolerance of physico-chemical stressors including elevated temperature, pH, salinity and phytotoxic metals/metalloids. Millerocaulis zamunerae thrived in wetlands preserved in the Jurassic geothermal systems of Santa Cruz Province, the same kind of environment in which Equisetum thermale Channing et al . was recorded previously. Ana Julia Sagasti [ anajusagasti@gmail.com ] División Paleobotánica, Facultad de Ciencias Naturales y Museo. Becaria Doctoral Consejo Nacional de Investigaciones Científicas y Técnicas, Paseo del Bosque S/N B1900FWA La Plata, Buenos Aires, Argentina. Juan García Massini [ massini112@yahoo.com.ar ] Centro Regional de Investigaciones Científicas y Transferencia Tecnológica de La Rioja (CRILAR), Provincia de La Rioja, UNLaR, SEGEMAR, UNCa, CONICET. Entre Ríos y Mendoza S/N, 5301 Anillaco, La Rioja Argentina. Ignacio H. Escapa [ iescapa@mef.org.ar ] Museo Paleontológico Egidio Feruglio, Consejo Nacional de Investigaciones Científicas y Técnicas, Av. Fontana 140, U9100GYO, Trelew, Chubut, Argentina. Diego M. Guido [ diegoguido@yahoo.com ] Instituto de Recursos Minerales (INREMI), Facultad de Ciencias Naturales y Museo, Universidad Nacional de La Plata. Consejo Nacional de Investigaciones Científicas y Técnicas. Calle 64 y 120, La Plata (1900), Argentina. Alan Channing [ channinga@gmail.com ] School of Earth & Ocean Sciences, Cardiff University, Cardiff CF10 3AT, UK.